The Management of Curriculum Based on Islamic Values - Fera Zihan Fadilah; Fitri Yati Naga; Softa Rizanah; Siti Nur Azizah; Galih Prayogi; Nurul Hidayati Murtafiah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to explore the concept, relevance, and implementation of an integrative curriculum based on Islamic values ​​in the context of modern education. An Islamic value-based curriculum is an educational approach that combines general knowledge with Islamic teachings holistically, aiming to produce a generation with Islamic character with intellectual, emotional, and spiritual intelligence. This study uses a qualitative method with literature studies to analyze the basic principles of the Islamic curriculum, such as monotheism, morals, balance, relevance, and integration of knowledge. The results of the study indicate that this curriculum has strong relevance in building the morals and character of students amidst the challenges of globalization. The implementation of a curriculum based on Islamic values ​​faces various challenges, including limited human resources and infrastructure, but has great potential to be implemented in Islamic educational institutions. This study recommends intensive training for teachers, development of Islamic-based teaching materials, and continuous evaluation of the implementation of this curriculum. This research is expected to provide a significant contribution to the development of Islamic education in Indonesia.